Design and Parameters Optimization of Key Components of Seed Peanut Shelling Test Bench Based on Cohesive Model - Chengtao Xu; Awei Zhu; Yanfen Liu; Shuqi Shang (Agriculture)
In order to improve the shelling efficiency of peanuts, the fracture mechanism of peanuts and the key components of the shelling test bench were studied. Firstly, the finite element method based on the cohesive element model was used to analyze the crack propagation of peanuts; the energy required for peanuts to crack was 0.06 J, and the maximum loading force was 30 N. Combined with the physical properties, mechanical properties, and shell-breaking energy of peanuts, the parameters of the two key components of the shell-breaking device and the adjustable grinding device were designed. The loading angle of the shell-breaking device was 30°, the mass of the rod was 1.5 kg, the mass of the hammer was 0.1 kg, the total length was 0.25 m, and the external contour of the grinding device was triangular. Through the field experiment, the single-factor test and the three-factor three-level regression test were designed, respectively, and the regression model of the removal rate and the damage rate was established. According to the response surface analysis of the regression model, when the feeding quantity is 12 pods/s, the speed of gear is 250 revolutions per minute, and the shelling clearance is 9.23 mm; the peanut removal rate reached 95.61%, and the kernel damage rate was 5.41%. However, the feeding amount was low and the damage rate was high, which could provide a reference for the future seed peanut sheller.